Ibn al-Haytham 11th century test of Visual Illusions - hamad, mozamil (Tafakkur, 2018)
The present study showed that Ibn Al-Haytham employed throughout Maqala III of Kitab al-Manazir or "The Book of optics" the term aghlat al-basar “error of visions” or visual illusions in modern psychological terms. Additionally, he described a series of I'tibar or experiments for measuring them. His test was applied to a group of mu'tabroun 1077 “8-70 years” from Bahrain. The number of males 498 “46,2%” and females 579 “53,8%”.  The group was selected with respect to seven age groups as well as five educational levels. The most remarkable finding of the present study is that Ibn al-Haytham's 11 th century replicates to 78.2% by the measures under modern conditions. The study also showed that Ibn al-Haytham's five experiments were reliable and valid.